Long Term Impact Of The Non Formal Pre School Education Component Of Icds On The Mental Status Of School Going Children - Sachar R K; Krishnan J; Bhatia R C; Raizada N; Dhot Ramnik; Soni R K; Gill P J S (Wolters Kluwer Medknow Publications, 1996)
Research Question: What is the long term impact of non formal pre-school education component of ICDS on the mental status of school children? Objective: To assess and compare the long-term impact of the preschool education component of ICDS on the mental development in rural and urban children in the school going age group (6-12 yrs). Study design: With and without non-formal education exposure. Setting: Two ICDS blocks one urban and one rural in Ludhiana district. Participants: School going children in age group 6-12 yrs. Sample Size: 360 children, (180 each from urban and rural) school going children from 30 schools. Study Variables: Age, Sex. Place of residence, previous ICDS attendance. Outcome Variable: present mental status by Raven Colored Progressive Matrices Test. Statistical Analysis: Mean and Standard Error of difference between means. Results: The children exposed to non-formal pre-school education through ICDS in younger life had better mental status than those who did not receive such stimulation. Urban children of higher age groups i.e, 8-10yrs, had better mental status than similar group of rural children. No sex difference was noted in between similar groups. Recommendation: Non-formal pre-school education component of ICDS is highly cost-effective measure in promoting mental development and serves very useful purpose in our present situation.